The Re-Invention of Tradition and the Marketing of Cultural Values - Oberholtzer, Cath (Anthropologica, 2022)
The concept of the invention of tradition has gained widespread acceptance and innumerable applications. However, consideration of the re-invention of tradition, particularly in the scope of material studies, has received minimal coverage. Increased production and marketing of Native-made "dream catchers" provides an excellent example. Derived from traditional baby charms no longer made to protect the developing infant, as a re-invented tradition this form is now rendered as earrings and ornamental items for car and home. For Natives, dream catchers serve a dual purpose in providing a cash return while simultaneously "marketing" Native values and spirituality.